Variability Independent of Mean Blood Pressure as an Electronic health record‐based Measure of Dementia Risk. (20th December 2022) - Driver, Matthew; Ebinger, Joseph; Cheng, Susan; Tan, Zaldy S
Abstract: Background: The risk of developing Alzheimer's Disease and Related Dementias (ADRD) is associated with visit‐to‐visit blood pressure (BP) variability, including variability independent of the mean (VIM). 1, 2 The association between ADRD and VIM has primarily been evaluated using standardized BP measurements from clinical trials and cohorts, rather than utilizing measurements from clinical practice, potentially limiting generalizability to the real‐world context. As such, we sought to evaluate the relationship between ADRD and BP VIM utilizing real‐world data collected from the electronic health record (EHR). Method: We studied all patients with repeated BP measurements and without a prior diagnosis of ADRD across ambulatory visits within a high‐volume academic healthcare system from 2013 to 2016. Using EHR data, we calculated BP VIM for all patients during the first 4 years of the study period and followed all patients through the end of 2019 or most recent office visit, whichever came first. The primary outcome of interest was incident ADRD, defined by presence of ICD‐10 codes for ADRD or prescription for dementia medication. We used multivariable adjusted Cox proportional hazards models to examine risk of incident ADRD associated with increasing BP VIM. Result: We identified 46, 703 patients with repeated BP measurements over 730, 721 ambulatory visits between 2013 and 2016. In multivariable analyses, higher levels of both systolic (HR, 95% CI: 1.26, 1.15‐1.38) and diastolic (1.15, 1.04‐1.27) BP VIM were positively associated with risk of incident dementia (Figure A) . In subgroup analyses, results were similar when stratified by age, diabetes, prior stroke, renal disease, and hypertension (Figures B‐D) . For both systolic (p = 0.036) and diastolic (p = 0.043) BP VIM, risk of incident dementia was higher among patients below the age of 60 compared to those 60 and older. Conclusion: Visit‐to‐visit variability in BP, a measure readily ascertainable from the EHR, is associated with increased risk for incident dementia independent of mean BP in the context of a high‐volume, real‐world patient care setting. These findings indicate the EHR derived VIM may serve as an additional tool in risk assessment for incident ADRD. Future research is needed to determine efficacy of targeted interventions aimed at lowering BP variability in clinical practice.